The Factors Influencing Young Voters in Determining The Choice: Case Study of Local Election in Bengkulu - Andi Azhar; Susyanto Susyanto (The Politics : Jurnal Magister Ilmu Politik Universitas Hasanuddin, 2015)
Abstract: The aim of this study was to create an explanatory model that allows analyzing the factors influencing young voters in determining the choice; case study in local election in Bengkulu. We also analyzed the combined relationship between these variables, together with age, and area of origin. We worked with a sample group of 400 young adults between the ages of 18-22 from the city of Bengkulu (Indonesia). The data was subjected to a structural equation modeling SEM analysis, which allowed for the corroboration of the following hypotheses: the higher the education level, the more the interest to choose; the more the experiences, the better the perception to choose; the better the tagline and propaganda, the more interest to choose; the closer the ethnic, the more interest to choose. The result showed that candidate who has more experiences is the most interest candidate to choose by young adult voter . The model obtained allows for discussion of the explanatory value of these variables.Keywords: Young Adult Voter, Structural Equation Modelling, Bengkulu